ASSESSMENT OF DIVERSITY AMONG OKRA (ABELMOSCHUS ESCULENTUS) GENOTYPES UNDER SALT STRESS - AHMAD, W; RAZA, MH; AZEEM, A; ABBAS, T; ANJUM, S; WAHOCHO, NA; JAMALI, MF; SULTAN, SM (Biological and Clinical Sciences Research Journal, 2024)
Okra is a summer annual, often cross-pollinated main vegetable of the tropical and subtropical areas The experiment was performed using 10 different Okra genotypes of unknown salt tolerance perspective sent to the salt state, to divide them into salt-tolerant, moderate-tolerant, and sensitive groups, based on their salt-tolerant ability. The tested genotypes were exposed to various growth stages such as germination and emergence, and seedling growth under high salt levels i.e. 0mM, 25 mM, 50mM, 75 mM, and 100mM to test the effects of salt pressure on low-salt okra genotypes. Vertical seedlings follow a pattern that reduces energy in terms of seedling roots and shoot lengths with fresh and dry weight. Examination of okra seed emergence revealed a declining trend in the percentage of emergence; plant biomass (fresh and dried) with seedling roots and shoot length. Based on the strength of the Okra genotypes of salt tolerance and results, okra genotypes OH-713, OH- 139, OH-138, and OH-001 were among the most tolerant and middle-tolerant groups including OH- 152, OH -597, and MD-02. The low-end middle-aged group was identified as including Sabzpari, Okra-7100 and Okra-7080. Following the results of our test. Therefore, from the final results these species of Okra are divided above the salt tolerance in saline soils and are suitable for salt-affected regions.